Ethnomathematical Insights into Rumah Gadang’s Building Form and Ornaments - Afriyanto Afriyanto; Ahmad Fauzan; Yerizon Yerizon; Edwin Musdi (AL-ISHLAH: Jurnal Pendidikan, 2024)
Ethnomathematics integrates cultural contexts into mathematical learning, enriching students' comprehension of mathematical concepts and their applications. This study explores the embodiment of ethnomathematical concepts within the architecture and ornamentation of Rumah Gadang in Luhak Tanah Datar, a traditional dwelling renowned for its intricate designs. Employing a qualitative research methodology, this investigation utilizes interviews, participatory observation, and document analysis to examine the contributions of two craftsmen. The primary objective is to elucidate the mathematical principles manifest in the structural and decorative elements of Rumah Gadang, with a focus on identifying specific mathematical ideas and concepts that are applicable to educational settings. Findings reveal that the architecture and decorations of Rumah Gadang incorporate various mathematical concepts, including counting, measuring, locating, designing, playing, and explaining, which are expressed through numbers, shapes, lines, geometric transformations, trigonometry, angles, and symmetry. This research not only highlights the presence of intricate mathematical ideas in traditional architecture but also suggests the potential of these findings to serve as valuable educational resources in teaching mathematics. Additionally, these insights provide a foundation for further ethnomathematical studies related to Rumah Gadang.